Silica aerogel composite aluminum silicate fiber felt and preparation method thereof

Through the composite and single-use wet forming process of modified silica aerogel powder and aluminum silicate fiber cotton, the problems of high preparation costs, complex processes and uneven aerogel dispersion in the prior art are solved, and the efficient preparation and excellent performance of silica aerogel composite aluminum silicate fiber felt are achieved.

CN119797886APending Publication Date: 2025-04-11ZIBO JINGNENG TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510299730.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing preparation process for silica aerogel composite aluminum silicate fiber felt has problems such as high cost, complex preparation process, and uneven dispersion of aerogels, making it difficult to achieve large-scale production and multi-scenario applications.

Method used

Modified silica aerogel powder is used to combine with aluminum silicate fiber cotton, and silica aerogel composite aluminum silicate fiber felt is prepared through a one-time wet molding process, and the uniform bonding of aerogel and fiber is improved by using dispersant and binder.

Benefits of technology

It realizes the efficient preparation of silica aerogel composite aluminum silicate fiber felt, with excellent thermal insulation, thermal insulation and mechanical properties, reduces preparation costs, simplifies process flow, and supports large-scale production and multi-scenario applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797886A_ABST
    Figure CN119797886A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of silicon dioxide aerogel composite materials, and particularly relates to a silicon dioxide aerogel composite aluminum silicate fiber felt and a preparation method thereof. The silicon dioxide aerogel composite aluminum silicate fiber felt is prepared from the following raw materials: silicon dioxide aerogel powder, aluminum silicate fiber cotton, a solvent, a dispersing agent and a binding agent, the silicon dioxide aerogel powder is prepared from the following raw materials: tetraethoxysilane, absolute ethyl alcohol, deionized water and a modifier. The silicon dioxide aerogel composite aluminum silicate fiber felt has excellent heat preservation, heat insulation and other properties, has excellent mechanical properties, can realize multi-scene application, and compared with a traditional silicon dioxide aerogel fiber felt preparation method, the method is rapid, efficient, low in cost and suitable for industrial production. The large-scale production of the silicon dioxide aerogel fiber felt can be realized; in addition, the invention further provides a preparation method, the preparation process is simple, and a final product can be prepared only through one-time forming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica aerogel composite materials, and particularly relates to a silica aerogel composite aluminum silicate fiber felt and a preparation method thereof. Background Art

[0002] Silica aerogel is a nanoporous material with extremely high porosity, large specific surface area, extremely low density and thermal conductivity. Silica aerogel is prepared by the sol-gel method and a special drying method. The preparation process includes aging treatment, freeze drying and heating treatment, which helps to form the unique nanoporous structure of the aerogel, thus giving it excellent thermal insulation properties. In order to improve the mechanical strength and application range of silica aerogel, it is often compounded with a fiber substrate to make aerogel felt. This composite material not only retains the thermal insulation properties of aerogel, but also solves the problem of low mechanical strength and fragility of aerogel itself.

[0003] At present, the existing silica aerogel composite aluminum silicate fiber felt technology is mostly a preform impregnation process, which adopts normal temperature and pressure drying or supercritical drying to prepare silica aerogel composite fiber felt materials with excellent thermal insulation performance, good mechanical strength and hydrophobicity. CN119390389A discloses a silica aerogel thermal insulation felt and a preparation method thereof, which adopts the process of: first preparing a premixed solution and a gel solution, then immersing the substrate in the gel solution, and finally obtaining the product after aging, solvent replacement and drying. The final product has excellent mechanical strength and thermal insulation performance, which solves the problem that the thermal insulation performance of the thermal insulation felt decreases due to the addition of inorganic reinforcing materials in the traditional way; although the supercritical drying process is the current mainstream process of aerogel composite felt, it has high cost, and the preparation process involves parameters such as air pressure and atmosphere, which is highly dangerous and the preparation process is complicated.

[0004] CN117902876A discloses a silica aerogel composite felt material, a preparation method and an application thereof, wherein the fiber felt composite silica wet gel is prepared by firstly performing negative pressure adsorption, and then performing hydrophobic modification to prepare the product, which enhances its thermal insulation performance and interface bonding ability to a certain extent. Although the silica aerogel composite aluminum silicate fiber felt prepared by the above process technology has good performance, it adopts a direct impregnation method, which belongs to an impregnation felt process, and the process is cumbersome, and there are problems such as uneven dispersion of silica aerogel in the fiber felt and high cost.

[0005] WO2024174731A1 discloses a thermal insulation material and a preparation method thereof, a thermal insulation component, a thermal insulation product, a battery and an electrical equipment, wherein the thermal insulation material is prepared by first dispersing and mixing the thermal insulation powder and the reinforcing phase fiber, and then performing compression molding. During the preparation process, the thermal insulation powder and the reinforcing phase fiber need to be processed, and the prepared product has good thermal insulation performance; however, the aerogel powder is extremely light, extremely small in size, and has poor toughness. This method is a simple physical mixing method, which cannot make the aerogel powder evenly compounded with the fiber, and the aerogel powder structure is easily damaged during the pressing process. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a silica aerogel composite aluminum silicate fiber felt, which has excellent thermal insulation and other properties, and at the same time has excellent mechanical properties, and can be applied in multiple scenarios. Compared with the traditional method of preparing silica aerogel fiber felt, this method is fast, efficient, and low in cost, and can realize the large-scale production of silica aerogel fiber felt; in addition, the present invention also provides a preparation method thereof, and the preparation process is simple, and the final product can be obtained by only one molding.

[0007] The silica aerogel composite aluminum silicate fiber felt of the present invention comprises the following raw materials in parts by mass: 1-2 parts of silica aerogel powder, 3-6 parts of aluminum silicate fiber cotton, 500-600 parts of solvent, 0.2-0.4 parts of dispersant, and 2-5 parts of binder; the silica aerogel powder is composed of the following raw materials in parts by mass: 10-15 parts of tetraethyl orthosilicate, 40-60 parts of anhydrous ethanol, 30-45 parts of deionized water, and 20-30 parts of a modifier.

[0008] The method for preparing the silica aerogel powder comprises the following steps: (1) Mixing tetraethyl orthosilicate, anhydrous ethanol and deionized water, and stirring evenly to obtain a mixture A; (2) adding an acid solution dropwise to adjust the pH value of the mixture A to 4-5 to obtain a mixture B, which was sealed and allowed to stand; (3) filtering the mixture B after standing to obtain a filter cake, dissolving the filter cake in anhydrous ethanol, adding a modifier, stirring, and standing to obtain a mixture C; (4) adding alkaline solution to adjust the pH value of the mixture C to 7-7.5, sealing and allowing to stand, and then filtering by pressure, and then drying the filter cake by microwave to obtain silica aerogel powder.

[0009] The modifier is prepared by mixing gamma-aminopropyltriethoxysilane and normal hexane, wherein the gamma-aminopropyltriethoxysilane accounts for 5-10 parts and the normal hexane accounts for 15-20 parts by weight.

[0010] In the step (2), the acid solution is a 0.1 mol / L hydrochloric acid solution or a nitric acid solution, and the sealed standing time is 11-13 hours.

[0011] In the step (4), the alkaline solution is a 0.1 mol / L ammonia solution, and the sealed standing time is 11-13 hours.

[0012] In the step (4), the specific parameters of microwave drying are: 30-35°C for 2-3h, 40-45°C for 2-3h, and 50-55°C for 1-2h.

[0013] The solvent is water, the dispersant is TY-ZJ01, and the binder is silica sol.

[0014] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, the aluminum silicate fiber cotton is mixed with the solvent and stirred to form a slurry, and then the silica aerogel powder, dispersant and binder are added and stirred for 10-15 minutes at a stirring speed of 1000-1500r / min. Finally, the silica aerogel composite aluminum silicate fiber felt is obtained by filtering and drying.

[0015] The drying and molding process parameters are: drying pressure 800-1000Pa, and drying and molding adopts staged temperature control drying, which is 30-35℃ insulation for 2-3h, 40-45℃ insulation for 2-3h, 50-55℃ insulation for 1-2h, and 130-140℃ insulation for 1-2h.

[0016] Furthermore, in the preparation method of the silica aerogel composite aluminum silicate fiber felt described in the present invention, the filtrate produced by filtration during the preparation process can be reused as a solvent after simple filtration treatment.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The silica aerogel composite aluminum silicate fiber felt of the present invention is prepared by modifying the silica aerogel so that the product has good mechanical strength and hydrophobicity, and compounding the silica aerogel with aluminum silicate fiber. The product has excellent thermal insulation performance and excellent mechanical properties.

[0018] (2) The preparation method of the silica aerogel composite aluminum silicate fiber felt of the present invention comprises mixing the slurry made of silica aerogel and aluminum silicate fiber cotton by a one-time wet molding method, adding dispersant TY-ZJ01 and silica sol. The dispersant TY-ZJ01 can make the silica aerogel more uniform in the aluminum silicate fiber slurry, and the silica sol can enhance the strength of the product after molding. Compared with the traditional preparation process of silica aerogel aluminum silicate fiber felt, the method has high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image of the silica aerogel composite aluminum silicate fiber felt prepared in Example 5 of the present invention.

[0020] Figure 2 This is a SEM image of the silica aerogel composite aluminum silicate fiber felt prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the embodiments and comparative examples. The raw materials used in the embodiments and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used are conventional methods in the art unless otherwise specified. The parts of the raw materials in the embodiments and comparative examples are all parts by mass.

[0022] The raw materials used in the embodiments and comparative examples are described as follows: Dispersant: TY-ZJ01, Jiaxing Tianyu New Materials Co., Ltd. Binder: silica sol, Shandong Yousuo Chemical Technology Co., Ltd.; Aluminum silicate fiber cotton: high-purity aluminum silicate spun fiber cotton, Shandong Minye Qihang New Material Technology Co., Ltd.; Aluminum silicate fiber felt: Zibo Chengnan Yongliang Thermal Insulation Refractory Materials Co., Ltd.

[0023] The method for preparing the silica aerogel powder comprises the following steps: (1) 10-15 parts of ethyl orthosilicate, 40-60 parts of anhydrous ethanol and 30-45 parts of deionized water are mixed and stirred to obtain a mixture A; (2) Add 0.1 mol / L hydrochloric acid solution or nitric acid solution to adjust the pH value of mixture A to 4-5 to obtain mixture B, which is sealed and allowed to stand for 11-13 hours; (3) After the mixture B has been allowed to stand, filter press to obtain a filter cake, dissolve the filter cake in anhydrous ethanol, add 20-30 parts of a modifier (5-10 parts of γ-aminopropyltriethoxysilane and 15-20 parts of n-hexane), stir, and then allow to stand to obtain a mixture C; (4) adding 0.1 mol / L ammonia solution to adjust the pH value of the mixture C to 7-7.5, sealing and standing for 11-13 h, and then filtering, and then subjecting the filter cake to microwave drying, keeping it warm at 30-35° C. for 2-3 h, keeping it warm at 40-45° C. for 2-3 h, and keeping it warm at 50-55° C. for 1-2 h, to obtain silica aerogel powder.

[0024] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, 3-6 parts of aluminum silicate fiber cotton are mixed with 500-600 parts of solvent, and stirred to form a slurry. Subsequently, 1-2 parts of silica aerogel powder, 0.2-0.4 parts of dispersant, and 2-5 parts of binder are added and stirred continuously. Then, the filter cake is dried and formed at a pressure of 800-1000Pa and a temperature gradient of 30-35°C for 2-3h, 40-45°C for 2-3h, 50-55°C for 1-2h, and 130-140°C for 1-2h to obtain a silica aerogel composite aluminum silicate fiber felt.

[0025] Example 1 The method for preparing the silica aerogel powder comprises the following steps: (1) 10 parts of tetraethyl orthosilicate, 40 parts of anhydrous ethanol and 30 parts of deionized water were mixed and stirred to obtain a mixture A; (2) adding 0.1 mol / L hydrochloric acid solution to adjust the pH value of mixture A to 4 to obtain mixture B, which was sealed and allowed to stand for 11 h; (3) After the mixture B has been allowed to stand, filter press the mixture to obtain a filter cake, dissolve the filter cake in anhydrous ethanol, add 20 parts of a modifier (5 parts of γ-aminopropyltriethoxysilane and 15 parts of n-hexane), stir, and then allow to stand to obtain a mixture C; (4) 0.1 mol / L ammonia solution was added dropwise to adjust the pH value of the mixture C to 7, the mixture was sealed and allowed to stand for 11 h, and then filtered. The filter cake was then microwave dried at 30° C. for 2 h, 40° C. for 2 h, and 50° C. for 1 h to obtain silica aerogel powder.

[0026] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, 3 parts of aluminum silicate fiber cotton were mixed with 500 parts of solvent and stirred to form a slurry. Then, 1 part of silica aerogel powder, 0.2 parts of dispersant TY-ZJ01 and 2 parts of binder silica sol were added. The stirring was continued and then filtered. The filter cake was dried and formed at a pressure of 800 Pa and a temperature gradient of 30°C for 2h, 40°C for 2h, 50°C for 1h and 130°C for 1h to obtain a 5mm thick silica aerogel composite aluminum silicate fiber felt.

[0027] Example 2 The method for preparing the silica aerogel powder comprises the following steps: (1) 13 parts of tetraethyl orthosilicate, 50 parts of anhydrous ethanol and 40 parts of deionized water were mixed and stirred to obtain a mixture A; (2) adding 0.1 mol / L nitric acid solution to adjust the pH value of mixture A to 5 to obtain mixture B, which was sealed and allowed to stand for 13 h; (3) After the mixture B has been allowed to stand, filter press the mixture to obtain a filter cake, dissolve the filter cake in anhydrous ethanol, add 26 parts of a modifier (8 parts of γ-aminopropyltriethoxysilane and 18 parts of n-hexane), stir, and then allow to stand to obtain a mixture C; (4) 0.1 mol / L ammonia solution was added dropwise to adjust the pH value of the mixture C to 7.5, and the mixture was sealed and allowed to stand for 13 h before being filtered. The filter cake was then microwave dried at 35° C. for 2 h, 45° C. for 2 h, and 55° C. for 1 h to obtain silica aerogel powder.

[0028] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, 4 parts of aluminum silicate fiber cotton were mixed with 550 parts of solvent and stirred to form a slurry. Then, 1 part of silica aerogel powder, 0.3 parts of dispersant TY-ZJ01, and 4 parts of binder silica sol were added. The stirring was continued and then filtered. The filter cake was dried and formed at a pressure of 900 Pa and a temperature gradient of 35°C for 2h, 45°C for 2h, 55°C for 1h, and 140°C for 1h to obtain a 5mm thick silica aerogel composite aluminum silicate fiber felt.

[0029] Example 3 The method for preparing the silica aerogel powder comprises the following steps: (1) 15 parts of tetraethyl orthosilicate, 60 parts of anhydrous ethanol and 45 parts of deionized water were mixed and stirred to obtain a mixture A; (2) adding 0.1 mol / L hydrochloric acid solution to adjust the pH value of mixture A to 5 to obtain mixture B, which was sealed and allowed to stand for 13 h; (3) After the mixture B has been allowed to stand, filter press the mixture to obtain a filter cake, dissolve the filter cake in anhydrous ethanol, add 30 parts of a modifier (10 parts of γ-aminopropyltriethoxysilane and 20 parts of n-hexane), stir, and then allow to stand to obtain a mixture C; (4) 0.1 mol / L ammonia solution was added dropwise to adjust the pH value of the mixture C to 7.5, and the mixture was sealed and allowed to stand for 13 h before being filtered. The filter cake was then microwave dried at 35° C. for 2 h, 45° C. for 2 h, and 55° C. for 1 h to obtain silica aerogel powder.

[0030] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, 6 parts of aluminum silicate fiber cotton were mixed with 600 parts of solvent and stirred to form a slurry. Subsequently, 2 parts of silica aerogel powder, 0.4 parts of dispersant TY-ZJ01, and 5 parts of binder silica sol were added. The stirring was continued and then filtered. The filter cake was dried and formed at a pressure of 1000Pa and a temperature gradient of 35°C for 2h, 45°C for 2h, 55°C for 1h, and 140°C for 1h to obtain a 5mm thick silica aerogel composite aluminum silicate fiber felt.

[0031] Example 4 The method for preparing the silica aerogel powder comprises the following steps: (1) 15 parts of tetraethyl orthosilicate, 60 parts of anhydrous ethanol and 45 parts of deionized water were mixed and stirred to obtain a mixture A; (2) adding 0.1 mol / L hydrochloric acid solution to adjust the pH value of mixture A to 5 to obtain mixture B, which was sealed and allowed to stand for 12 h; (3) After the mixture B has been allowed to stand, filter press the mixture to obtain a filter cake, dissolve the filter cake in anhydrous ethanol, add 30 parts of a modifier (10 parts of γ-aminopropyltriethoxysilane and 20 parts of n-hexane), stir, and then allow to stand to obtain a mixture C; (4) 0.1 mol / L ammonia solution was added dropwise to adjust the pH value of the mixture C to 7.5, and the mixture was sealed and allowed to stand for 12 h before filter pressing. The filter cake was then microwave dried at 35° C. for 2 h, 45° C. for 2 h, and 55° C. for 1 h to obtain silica aerogel powder.

[0032] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, 3 parts of aluminum silicate fiber cotton were mixed with 600 parts of solvent and stirred to form a slurry. Subsequently, 2 parts of silica aerogel powder, 0.4 parts of dispersant TY-ZJ01, and 5 parts of binder silica sol were added. The stirring was continued and then filtered. The filter cake was dried and formed at a pressure of 800 Pa and a temperature gradient of 35°C for 2h, 45°C for 2h, 55°C for 1h, and 140°C for 1h to obtain a 5mm thick silica aerogel composite aluminum silicate fiber felt.

[0033] Example 5 The method for preparing the silica aerogel powder comprises the following steps: (1) 15 parts of tetraethyl orthosilicate, 60 parts of anhydrous ethanol and 45 parts of deionized water were mixed and stirred to obtain a mixture A; (2) adding 0.1 mol / L hydrochloric acid solution to adjust the pH value of mixture A to 5 to obtain mixture B, which was sealed and allowed to stand for 13 h; (3) After the mixture B has been allowed to stand, filter press the mixture to obtain a filter cake, dissolve the filter cake in anhydrous ethanol, add 30 parts of a modifier (10 parts of γ-aminopropyltriethoxysilane and 20 parts of n-hexane), stir, and then allow to stand to obtain a mixture C; (4) 0.1 mol / L ammonia solution was added dropwise to adjust the pH value of the mixture C to 7.5, and the mixture was sealed and allowed to stand for 13 h before filter pressing. The filter cake was then microwave dried at 35° C. for 3 h, 45° C. for 3 h, and 55° C. for 2 h to obtain silica aerogel powder.

[0034] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: First, 6 parts of aluminum silicate fiber cotton were mixed with 600 parts of solvent and stirred to form a slurry. Subsequently, 2 parts of silica aerogel powder, 0.4 parts of dispersant TY-ZJ01, and 5 parts of binder silica sol were added. The stirring was continued and then filtered. The filter cake was dried and formed at a pressure of 800 Pa and a temperature gradient of 35°C for 3h, 45°C for 3h, 55°C for 2h, and 140°C for 2h to obtain a 5mm thick silica aerogel composite aluminum silicate fiber felt.

[0035] Comparative Example 1 This comparative example is the same as Example 5, except that, in this comparative example, the preparation of the silica aerogel powder does not require a microwave drying step, and the mixture C obtained in step (3) is adjusted to a pH value of 7.5 with a 0.1 mol / L ammonia solution, and the mixture is sealed and allowed to stand for 13 h to obtain a silica aerogel mixture.

[0036] The method for preparing the silica aerogel composite aluminum silicate fiber felt comprises the following steps: The aluminum silicate fiber felt with a thickness of 5 mm was immersed in the silica aerogel mixture for 1 hour, and then dried at the following temperatures: 35°C for 3 hours, 45°C for 3 hours, 55°C for 2 hours, and 140°C for 2 hours to obtain a silica aerogel composite aluminum silicate fiber felt with a thickness of 5 mm.

[0037] Comparative Example 2 This comparative example is the same as Example 5, except that, during the preparation process of the silica aerogel composite aluminum silicate fiber felt, there is no need to add the binder silica sol, and the remaining raw material portions and the preparation process are the same as those of Example 5.

[0038] The silica aerogel composite aluminum silicate fiber felt obtained in this comparative example had cracks on the surface after drying, and the surface was loose and had poor strength.

[0039] Comparative Example 3 This comparative example is the same as Example 5, except that, during the preparation of the silica aerogel composite aluminum silicate fiber felt, no dispersant TY-ZJ01 is required to be added, and the remaining raw material portions and the preparation process are the same as those of Example 5.

[0040] In the process of preparing the silica aerogel composite aluminum silicate fiber felt in this comparative example, the silica aerogel powder was suspended on the surface of the slurry and could not be mixed into the solution to combine with the aluminum silicate fiber cotton.

[0041] The silica aerogel composite aluminum silicate fiber felt prepared in Examples 1-5 and Comparative Examples 1-3 were tested for thermal conductivity according to GB / T10294-2008, and for tensile strength according to GB / T17911-2018, and the results are shown in Table 1; the thermal insulation properties of Examples 1-5 and Comparative Examples 1-2 were tested according to T / CSTM00193-2020, and the results are shown in Table 2.

[0042] Table 1 Test results of thermal conductivity and tensile strength of silica aerogel composite aluminum silicate fiber felt

[0043] Table 2 Silica aerogel composite aluminum silicate fiber felt thermal insulation test results

[0044] It can be seen from Table 1 and Table 2 that the silica aerogel composite aluminum silicate fiber felt prepared in the present invention has a low thermal conductivity and excellent tensile strength, which proves that it can effectively block the transfer of heat and has excellent thermal insulation, heat insulation and mechanical properties. In particular, the silica aerogel composite aluminum silicate fiber felt prepared in Example 3 and Example 5 has the lowest thermal conductivity, which proves that the higher the content of silica aerogel and aluminum silicate fiber cotton, the lower the thermal conductivity of the silica aerogel composite aluminum silicate fiber felt prepared therefrom; By comparing Example 5 with Comparative Example 2, it can be obtained that due to Comparative Example 3, the thermal conductivity of the silica aerogel composite aluminum silicate fiber felt prepared in Example 5 is lower than that of the composite aluminum silicate fiber felt prepared in Example 5. 2 No binder is added, resulting in extremely low tensile strength of the molded product and easy breakage. Although its thermal insulation effect is the same as that of the embodiment, its poor strength leads to poor actual use effect. By comparing Example 5 with Comparative Example 3, it can be obtained that since no dispersant is added in Comparative Example 3, the silica aerogel powder is suspended on the surface of the slurry and cannot be mixed into the solution to fully combine with the aluminum silicate fiber cotton. Only a trace amount of silica aerogel powder is attached to the surface of the aluminum silicate fiber cotton, resulting in extremely low silica aerogel content in the final product, and thus poor thermal conductivity of the product.

[0045] By comparing Example 5 with Comparative Example 1, it can be seen that under the same raw materials, the product prepared by the impregnation method has a higher thermal conductivity and poorer thermal insulation performance. The reason is that Figure 1It can be seen that in the silica aerogel composite aluminum silicate fiber felt prepared in Example 5, the silica aerogel powder particles are not only attached to the aluminum silicate fibers, but also form larger aggregated particles filled in the criss-crossed aluminum silicate fibers. This effective filling greatly plays the role of the aerogel powder and improves the thermal insulation of the composite material. Figure 2 It can be seen that in the silica aerogel composite aluminum silicate fiber felt prepared in Comparative Example 1, the silica aerogel powder particles are only attached to the surface of the aluminum silicate fiber, and no further filling is formed in the aluminum silicate fiber, resulting in a low content of silica aerogel powder particles in the product, which reduces the thermal insulation of the product to a certain extent and affects the thermal conductivity of the product. The comprehensive thermal conductivity and thermal insulation test results further prove that the performance of the samples prepared by wet molding is significantly better than that of the impregnation method.

Claims

1. A silica aerogel composite aluminum silicate fiber felt, characterized in that: The raw materials include the following parts by weight: 1-2 parts of silica aerogel powder, 3-6 parts of aluminum silicate fiber cotton, 500-600 parts of solvent, 0.2-0.4 parts of dispersant, and 2-5 parts of binder; The silicon dioxide aerogel powder is composed of the following raw materials in parts by weight: 10-15 parts of ethyl orthosilicate, 40-60 parts of anhydrous ethanol, 30-45 parts of deionized water, and 20-30 parts of a modifier.

2. The silica aerogel composite aluminum silicate fiber felt according to claim 1, characterized in that: The method for preparing the silica aerogel powder comprises the following steps: (1) Mixing tetraethyl orthosilicate, anhydrous ethanol and deionized water, and stirring evenly to obtain a mixture A; (2) adding an acid solution dropwise to adjust the pH value of the mixture A to 4-5 to obtain a mixture B, which was sealed and allowed to stand; (3) filtering the mixture B after standing to obtain a filter cake, dissolving the filter cake in anhydrous ethanol, adding a modifier, stirring, and standing to obtain a mixture C; (4) adding alkaline solution to adjust the pH value of the mixture C to 7-7.5, sealing and allowing to stand, and then filtering by pressure, and then drying the filter cake by microwave to obtain silica aerogel powder.

3. The silica aerogel composite aluminum silicate fiber felt according to claim 1, characterized in that: The modifier is prepared by mixing gamma-aminopropyltriethoxysilane and normal hexane, wherein the gamma-aminopropyltriethoxysilane accounts for 5-10 parts and the normal hexane accounts for 15-20 parts by weight.

4. The silica aerogel composite aluminum silicate fiber felt according to claim 2, characterized in that: In the step (2), the acid solution is a 0.1 mol / L hydrochloric acid solution or a nitric acid solution, and the sealed standing time is 11-13 hours.

5. The silica aerogel composite aluminum silicate fiber felt according to claim 2, characterized in that: In the step (4), the alkaline solution is a 0.1 mol / L ammonia solution, and the sealed standing time is 11-13 hours.

6. The silica aerogel composite aluminum silicate fiber felt according to claim 2, characterized in that: In the step (4), the specific parameters of microwave drying are: 30-35°C for 2-3h, 40-45°C for 2-3h, and 50-55°C for 1-2h.

7. The silica aerogel composite aluminum silicate fiber felt according to claim 1, characterized in that: The solvent is water, the dispersant is TY-ZJ01, and the binder is silica sol.

8. A method for preparing the silica aerogel composite aluminum silicate fiber felt according to any one of claims 1 to 7, characterized in that: The following steps are involved: First, the aluminum silicate fiber cotton is mixed with the solvent and stirred to form a slurry, and then the silica aerogel powder, dispersant and binder are added, and stirring is continued for 10-15 minutes at a stirring speed of 1000-1500r / min. Finally, the silica aerogel composite aluminum silicate fiber felt is obtained by filtering and drying.

9. The method for preparing the silica aerogel composite aluminum silicate fiber felt according to claim 8, characterized in that: The drying and molding process parameters are: drying pressure 800-1000Pa, and drying and molding adopts staged temperature control drying, which is 30-35℃ insulation for 2-3h, 40-45℃ insulation for 2-3h, 50-55℃ insulation for 1-2h, and 130-140℃ insulation for 1-2h.

Citation Information

Patent Citations

  • Silica aerogel composite felt material, preparation method and application thereof

    CN117902876A

  • Silicon dioxide aerogel insulation felt and preparation method thereof

    CN119390389A

  • Heat insulation material, preparation method therefor, heat insulation member, heat insulation product, battery and electrical apparatus

    WO2024174731A1

  • Basalt fiber and aerogel powder composite heat insulating material and preparation method thereof

    CN103073237A

  • Method for quickly preparing self-hydrophobic SiO2 aerogel by using microwaves

    CN104556064A